2019
DOI: 10.21203/rs.2.14816/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of Bacillus acidophilus in osteoporosis and its roles in osteocyte proliferation and differentiation

Abstract: The microbes play an important role to physiological activities of human. Osteoporosis is one of the most closely relationship diseases with the elderly. In recent years, the studies found that gut microbiota can cause osteoporosis. These microbes may affect activity of osteoclasts and osteoblasts to affect bone metabolism. We selected 5 health people and 10 osteoporosis patients and found that the diversity of gut microbiota in osteoporosis patients are decreased and imbalance with lower abundance of lactobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Rahman et al exhibited that conjugated linoleic acid inhibits osteoclastogenesis by modulating RANKL signaling [ 48 ]. Chen et al revealed that the supernatant of Lactobacillus acidophilus and butanoic acids stimulated the proliferation, differentiation, and maturity of osteoblasts MC3T3-E1 cells was, increased the activity of alkaline phosphatase, elevated concentration of osteocalcin, and the expression of RUNX2, WNT2 and CTNNB1 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rahman et al exhibited that conjugated linoleic acid inhibits osteoclastogenesis by modulating RANKL signaling [ 48 ]. Chen et al revealed that the supernatant of Lactobacillus acidophilus and butanoic acids stimulated the proliferation, differentiation, and maturity of osteoblasts MC3T3-E1 cells was, increased the activity of alkaline phosphatase, elevated concentration of osteocalcin, and the expression of RUNX2, WNT2 and CTNNB1 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rahman et al exhibited that conjugated linoleic acid inhibits osteoclastogenesis by modulating RANKL signaling (42). Chen et al revealed that the supernatant of Lactobacillus acidophilus and butanoic acids stimulated the proliferation, differentiation, and maturity of osteoblasts MC3T3-E1 cells was, increased the activity of alkaline phosphatase, elevated concentration of osteocalcin, and the expression of RUNX2, WNT2 and CTNNB1 (43).…”
Section: Discussionmentioning
confidence: 99%